The influence of free cash flow, capital structure, investment opportunities, and company growth on dividend policy - Sawal, Nuning Safitri M.; Ohorella, Rizki Wahyu Utami; Meliana, Meliana (Journal of Contemporary Accounting, 2025)
This study examines the influence of free cash flow, capital structure, investment opportunities, and firm growth on dividend policy among mining companies listed on the Indonesia Stock Exchange (IDX) over the observation period. The research applies multiple regression analysis based on secondary data derived from financial statements and annual reports. The findings reveal that free cash flow, capital structure, and firm growth do not have a significant impact on dividend policy. In contrast, investment opportunities show a positive and meaningful effect on dividend decisions. Collectively, these variables are found to influence dividend policy, although the model explains only a limited portion of its variation, indicating that other factors beyond the scope of this study also play a role. The results suggest that investment opportunities serve as an important consideration for management in determining dividend policy, while free cash flow, capital structure, and firm growth are not the primary determinants.